Duration of breastfeeding, but not timing of solid food, reduces the risk of overweight and obesity in children aged 24 to 36 months: Findings from an Australian cohort study - Bell, S.; Yew, S.; Devenish, G.; Ha, D.; Do, L.; Scott, Jane (Molecular Diversity Preservation International (MDPI), 2018)
Â© 2018 by the authors. Licensee MDPI, Basel, Switzerland. This study aimed to determine whether breastfeeding duration and the timing of solid food were independently associated with being overweight or obese in early childhood. Subjects were 953 children participating in the Study of Mothers and Infants Life Events Affecting Oral Health (SMILE) birth cohort study, based in Adelaide, Australia. Socio-demographic information and data on breastfeeding duration and age of introduction of solid food were collected at birth, 3, 4, 6, 12, and 24 months via mailed or online questionnaires completed by mothers. The weight and height of children were measured at a dental examination when children were aged between 24 and 36 months. Body mass index was calculated, and children were categorised into weight groups according to the World Health Organization growth standards. Multivariable logistic regression analysis was conducted, adjusting for maternal age at birth, education, socio-economic status, pre-pregnancy weight, smoking in pregnancy, method of delivery, and childâ€™s birthweight. Risk of overweight/obesity was independently associated with maternal pre-pregnancy BMI, smoking in pregnancy, and birthweight. Children that were breastfed for 12 months or more had a significantly lower risk of being overweight/obese than those breastfed for less than 17 weeks (AOR 0.49; 95%CI 0.27, 0.90; p for trend =0.009). Age of introduction of solid food, however, was not associated with the risk of being overweight/obese at 24 to 36 months. This study provides further evidence of an inverse relationship between breastfeeding and risk of overweight/obesity, however, no association with the timing of solid food was detected.